Sleep and brain evolution across the human lifespan: A mutual embrace - Mutti, Carlotta; Misirocchi, Francesco; Zilioli, Alessandro; Rausa, Francesco; Pizzarotti, Silvia; Spallazzi, Marco; Parrino, Liborio (Frontiers in Network Physiology, 2022)
Sleep can be considered a window to ascertain brain wellness: it dynamically changes with brain maturation and can even indicate the occurrence of concealed pathological processes. Starting from prenatal life, brain and sleep undergo an impressive developmental journey that accompanies human life throughout all its steps. A complex mutual influence rules this fascinating course and cannot be ignored while analysing its evolution. Basic knowledge on the significance and evolution of brain and sleep ontogenesis can improve the clinical understanding of patient’s wellbeing in a more holistic perspective. In this review we summarized the main notions on the intermingled relationship between sleep and brain evolutionary processes across human lifespan, with a focus on sleep microstructure dynamics.